Ecology and Management of Lake Naivasha, Kenya, in Relation to Climatic Change, Alien Species' Introductions, and Agricultural Development - Harper, David M.; Mavuti, Kenneth M.; Muchiria, Mucai S. (University Of Nairobi, 1990)
Lake Naivasha is an important freshwater resource for Kenya's foreign-currency-earning agriculture and tourism, and for water-supply. It has always experienced extensive water-level fluctuations as a consequence of irregular rainfall patterns that are affected by continental-scale climatic events, and its communities — particularly of aquatic plants — were adapted to these changes.